Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif